2003
DOI: 10.1081/css-120021307
|View full text |Cite
|
Sign up to set email alerts
|

Improving Effectiveness Of Seedrow-placed Urea With Urease Inhibitor And Polymer Coating For Durum Wheat And Canola

Abstract: Seedrow-placed urea minimizes soil disturbance in reduced tillage systems, but it generally decreases emergence at nitrogen (N) rates adequate for optimum crop yield. The objective of this study was to determine the influence of coating urea fertilizer granules with a urease inhibitor or a polymer on the emergence and seed yield of durum wheat (Triticum turgidum L.) and canola (Brassica napus L.) with seedrow-placed urea, and to determine the appropriate rate of Agrotaine coating for seedrow-placement. Protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…Grain yield in these two sites over the 3 yr of the experiment was generally higher when NBPT-treated urea was used rather than untreated urea. Malhi et al (2003) observed a similar improvement in seedling emergence and grain yield when NBPT-treated urea was seed-placed with durum wheat and canola. These authors carried out field experiments in 2000 at three sites in Saskatchewan that included comparison of seed-placed NBPT-treated and polymer-coated urea to uncoated urea.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Grain yield in these two sites over the 3 yr of the experiment was generally higher when NBPT-treated urea was used rather than untreated urea. Malhi et al (2003) observed a similar improvement in seedling emergence and grain yield when NBPT-treated urea was seed-placed with durum wheat and canola. These authors carried out field experiments in 2000 at three sites in Saskatchewan that included comparison of seed-placed NBPT-treated and polymer-coated urea to uncoated urea.…”
supporting
confidence: 55%
“…Reduction in seedling damage has been attributed to an increase in the duration of urea diffusion away from the seedrow as a result of the reduction in urea hydrolysis with application of NBPT (Malhi et al 2003); it has been shown to occur with a number of crops, such as barley (Pauly et al 1996;Grant and Bailey 1999), wheat (Xiaobin et al 1995;Pauly et al 1996;Malhi et al 2003), canola (Pauly et al 1996;Malhi et al 2003) and corn (Schlegel 1991). Grant and Bailey (1999) observed that improvement in seed-placed urea safety with NBPT was dependent on the environmental conditions occurring after seeding.…”
Section: Discussionmentioning
confidence: 99%
“…Mahli et al (2003) found that urea coated with polymer tended to provide better seedling protection than urea coated with urease inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Urea can damage the seedlings after it hydrolyses by the enzyme urease, where the produced ammonia (NH 3 ) and ammonium (NH4+) can cause ammonia toxicity and osmotic damage (Bremner, 1995). Urea toxicity can be reduced by applying urease inhibitor to the fertilizer granule (Grant and Bailey, 1999;Malhi et al, 2003, Karamanos et al, 2004. This study was conducted in the main agricultural plain (Thessaly) to evaluate the effect of new types of fertilizers containing urease inhibitor on the yield of the main arable crops (durum wheat, cotton and maize) in Greece.…”
Section: Introductionmentioning
confidence: 99%